Potensi Limbah Tanaman Aren (Arenga Pinnata) Sebagai Sumber Daya Ekologis Dan Ekonomis Di Kawasan Hutan Kemasyarakatan (HKm) - Febriana Tri Wulandari; Suwardji Suwardji; Aluh Nikmatullah (LPPM Universitas Mataram, 2026)
his study aims to analyze the potential of aren palm (Arenga pinnata) waste as an ecological and economic resource within a circular economy framework in the Aik Bual Community Forest (HKm), West Nusa Tenggara, Indonesia. The research employed a literature review approach combined with secondary data analysis derived from farmer group observations and relevant scientific literature on aren biomass utilization. The results indicate that various types of aren waste, including fiber, fronds, sap residue, stems, and fruit shells, have significant potential to be converted into value-added products. The estimated total waste generated from 433 aren trees reaches approximately 22.43 tons per year, which can be processed into 6.73 tons of biobriquettes or around 33,645 units, with an estimated economic value of IDR 84 million annually. These findings demonstrate that aren waste utilization not only contributes to increasing rural income but also supports waste reduction, local economic strengthening, clean energy transition, and environmental conservation. The development of appropriate technology, institutional strengthening, and supportive policy frameworks are essential for the sustainable optimization of aren waste utilization